Profile of Colles Fracture Patients at Dr. Soetomo General Hospital - Andre Triade Desnantyo; Imam Subadi; Fiequria Asri Ersyana (Health Notions, 2021)
Colles fracture is the most common wrist fracture, with a incidence of 24% among the working population, where fracture through the radius cause the distal part to be displaced radially dan dorsally. These fractures of the distal radius are often caused by a fall on the outstretched hand with the wrist in dorsoflexion, causing tension on the volar aspect of the wrist, causing the fracture to extend toward the back of the hand. The incidence of Colles fracture is most common in adults over the age of 50 years and more common in women then men because of the onset of postmenopausal osteoposrosis where falls with outstretched arms are the most common cause. The purpose of this study was to determine the profile of patients with Colles fracture at Dr Soetomo Hospital Surabaya for the period January 2019 – 2020.  This research is a descriptive study with a cross-sectional approach that takes secondary data. In this study, there were 121 case samples after the inclusion and exclusion criteria were carried out. The conclusion of this study, based on the Frykman classification, Colles fracture moat often occur in Frykman 1. Based on the age, Colles fracture most often occur in late elderly patients, namely at the age of 56-65 years. According to mode of injury, Colles fracture are the most common in patients who fall. Based on the treatment given to the patient, most Colles fracture patients were treated with a combination of operative and conservative.Keywords: colles fracture; profile